Konsep Kearifan Lokal dan Ilmu Pengetahuan Penggunaan Materi Berbasis Lokal Kurikulum Berbasis Cinta pada Madrasah Ibtidaiyah - Khoirun Nisa; Asqia Viani; Ahmad Zainuri; Frika Fatimah Zahra (INDO PUBLISHING, 2025)
The Love-Based Curriculum integrates values of compassion, character formation, and Islamic spirituality into all learning activities. This study was conducted to examine how the concept of local wisdom is applied within the context being investigated and scientific knowledge through the use of locally based learning materials within the Love-Based Curriculum implemented in Madrasah Ibtidaiyah. Using a qualitative approach through direct observation, in-depth interviews, and the examination of relevant documents, this research explores how teachers develop and utilize learning materials derived from local cultural contexts to enhance students’ understanding of scientific concepts. The findings indicate that local-based materials significantly increase student engagement, foster appreciation for regional culture, and strengthen the connection between scientific knowledge and local wisdom values. Furthermore, the integration with the Love-Based Curriculum supports the development of students’ moral character, environmental awareness, and contextual understanding of their surroundings. Thus, the incorporation of local wisdom in learning contributes positively to students’ intellectual, emotional, and spiritual growth in Madrasah Ibtidaiyah.